Creating an ownership society? Social security reform and the temporalities of libertarian rhetoric - Simone Knewitz (Finance and Society, 2018)
Former US president George W. Bush's idea of the United States as an "ownership society" can be considered as the rhetorical apex of a conservative, libertarian push for a more market- driven restructuring of American social institutions. Reformers in the Bush administration particularly targeted Social Security, a popular American institution and signature achievement of the New Deal era, aiming to replace a system of solidarity with one of individual responsibility and partial privatization. Returning to the time of the early 2000s, this article analyzes the rhetoric of the ownership society as a libertarian utopian social vision - a future, more perfect community the United States should aspire to grow into. It argues that the political discourse on Social Security propagated by the Bush administration relied on rhetorical strategies characterized by an engagement of temporalities. On the one hand, ownership discourse invoked the nation's past achievements and traditional values secured during the American Revolution and guaranteed in the nation's founding documents. On the other hand, the administration framed the alleged urgency of the reforms by making projections about the future and using these to raise questions about the present system of Social Security provision. In this way, earlier debates over Social Security reform provide a valuable perspective on the contemporary nexus of finance and temporality.
Keywords: 300; Social security; Bush administration; libertarianism; ownership society; political rhetoric